2017
DOI: 10.1103/physrevb.95.014204
|View full text |Cite
|
Sign up to set email alerts
|

New quantum transition in Weyl semimetals with correlated disorder

Abstract: A Weyl semimetal denotes an electronic phase of solids in which two bands cross linearly. In this paper we study the effect of a spatially correlated disorder on such a phase. Using a renormalization group analysis, we show that in three dimensions, three scenarios are possible depending on the disorder correlations. A standard transition is recovered for short range correlations. For disorder decaying slower than 1/r 2 , the Weyl semimetal is unstable to any weak disorder and no transition persists. In betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…Apart from short-range disorder, there might be disorder with long-range correlation in various SMs 50,107,[115][116][117][118][119] . The most frequently encountered is Coulomb impurity, which is defined in a similar way to that of RSP, but is spatially long-ranged.…”
Section: Influence Of Coulomb Impurity On Triple-wsmmentioning
confidence: 99%
“…Apart from short-range disorder, there might be disorder with long-range correlation in various SMs 50,107,[115][116][117][118][119] . The most frequently encountered is Coulomb impurity, which is defined in a similar way to that of RSP, but is spatially long-ranged.…”
Section: Influence Of Coulomb Impurity On Triple-wsmmentioning
confidence: 99%
“…51 The effect of disorder correlations on the semimetal-diffusive metal transition was investigated in Ref. 52. It was found that for a < 2 the semimetal phase is always unstable while for 2 < a < a c ≈ 2.8 disorder drives the transition to a new universality class, whose critical exponents depend on a.…”
Section: Introductionmentioning
confidence: 99%
“…Stability regions of different FPs in the plane (a = 2 + δ, d = 2 + ε) 52. For a < 2 the Gaussian FP is unstable and the RG flow exhibits runaway reflecting instability of the semimetal phase in the case of very LR correlated disorder: a diffusive metal phase is settled for arbitrary weak disorder and the transition disappears.…”
mentioning
confidence: 97%
“…Hence we believe that our work sheds new light on the description of critical non-Gaussian disorder fluctuations in quantum systems beyond the disorderdriven semimetal-diffusive metal phase transition.Here we focus on the transition between a pseudoballistic semimetal phase with a vanishing density of states (DOS) at the nodal point and a diffusive metal phase with a finite DOS at zero energy [16][17][18][19][20][21][22][23]. The fieldtheoretic description of this transition using both replica and SUSY approaches [24][25][26][27] implies that in the absence of scattering between different nodal points the transition is controlled by a perturbative in ε = d − 2 FP of the d-dimensional U (N ) Gross-Neveu (GN) model taken in the unusual limit of a vanishing number of fermion flavors N → 0. As for the Anderson transition, numerical studies [28][29][30][31][32] demonstrate quantitative discrepancies with the predictions of the GN model [24][25][26] which grow with the order of approximation.…”
mentioning
confidence: 99%